Trace Element-Augmented Titanium Implant With Targeted Angiogenesis and Enhanced Osseointegration in Osteoporotic Rats - Yan, Ran; Li, Jinhua; Wu, Qianju; Zhang, Xiangkai; Hu, Longwei; Deng, Yuwei; Jiang, Ruixue; Wen, Jin; Jiang, Xinquan (Frontiers in Chemistry, 2022)
Deteriorated bone quality in osteoporosis challenges the success of implants which are in urgent need for better early osseointegration as well as antibacterial property for long-term stability. As osteoporotic bone formation tangles with angiogenic clues, the relationship between osteogenesis and angiogenesis has been a novel therapy target for osteoporosis. However, few designs of implant coatings take the compromised osteoporotic angiogenic microenvironment into consideration. Here, we investigated the angiogenic effects of bioactive strontium ions of different doses in HUVECs only and in a co-culture system with BMSCs. Strontium ions in proper dose (0.2-1 mM) could enhance the secretion of VEGFA and Ang-1 in HUVECs as well as in the co-culture system with BMSCs, exhibiting potential to create an angiogenic microenvironment in early stage benefiting following osteogenesis. Based on the dose screening, we fabricated a bioactive titanium surface doped with zinc and different doses of strontium by plasma electrolytic oxidation (PEO), for the establishment of a microenvironment favoring osseointegration for osteoporosis. The dual bioactive elements augmented titanium surfaces induced robust osteogenic differentiation and enhanced antimicrobial properties. Augmented titanium implant surfaces exhibited improved bone formation and bone-implant contact under comprehensive assessment of in vivo bone-implant interface. In conclusion, zinc and strontium augmented titanium surface benefits the osseointagration in osteoporosis via promoting osteogenic differentiation, exerting antibacterial efficacy and stimulating early angiogenesis.